Exploring cost-effective management measures for reducing risks to threatened sharks in a problematic longline fishery - Booth, H; Powell, G; Yulianto, I; Simeon, B; Muhsin; Adrianto, L; Milner-Gulland, EJ (Elsevier, 2022)
Many shark and ray species (Class Chondrichthyes, herein ‘sharks’) are threatened by overfishing. Tackling this requires implementation of context-specific fisheries management measures, which are both technically effective and socio-economically feasible. Here we explore the cost-effectiveness of various input-oriented management measures for mitigating capture of seven priority shark taxa (i.e., threatened and CITES-listed species) in a small-scale longline mixed-species shark fishery in Indonesia, where there is a need to balance difficult trade-offs between conservation and socio-economic objectives. We apply Boosted Regression Trees (BRT) to analyse five years of landings and profit data, to identify and assess the relative influence of different plausible management measures (e.g., effort restrictions, gear restrictions, spatio-temporal closures). We then use predictive models to inform a semi-quantitative assessment of the hypothetical cost-effectiveness of these management measures, based on the estimated conservation benefits (reduced risk of capture of priority taxa) and socio-economic cost (relative profit foregone). Our results show that fishery closures in January–March, depth limits at <100 m, hook limits at <500 hooks, and gear restrictions on bottom longlines could have the greatest relative conservation impact for lowest profit foregone. However, there are clear trade-offs between taxa, with these measures primarily benefiting Critically Endangered bottlenose wedgefish (Rhynchobatus Australiae) and scalloped hammerheads (Sphyrna lewini), while potentially increasing pressure on Vulnerable silky sharks (Carcharhinus falciformis) and Endangered mako sharks (Isurus spp.). When shark fishing is important for economic welfare, and entire fishery closures or buy-outs are unfeasible, managing small-scale shark fisheries for multiple outcomes may require hard choices. This may require prioritising slow-growing Critically Endangered taxa for protection – by restricting fishing during seasons and at depths in which they are most susceptible to capture – while faster-growing taxa can continue to provide benefits for coastal communities.